THE PEDAGOGICAL POTENTIAL OF TRADITIONAL NATIONAL GAMES IN INCREASING THE PHYSICAL ACTIVITY OF PRIMARY SCHOOL STUDENTS - Allaberdiyeva Nilufar Anvar qizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the pedagogical potential of using traditional national games to increase the physical activity of primary school students. Folk games play an important role in developing such physical qualities as agility, coordination, speed, balance, endurance, and overall motor skills in children of primary school age. Traditional national games are not only an effective means of physical education, but also serve as an important pedagogical factor in developing teamwork, discipline, mutual respect, loyalty to national values, and social activity among students. The article discusses the educational and upbringing significance of traditional national games, the mechanisms of their use in physical education lessons and extracurricular activities, as well as the methodological approaches of the teacher.